Outcome of in-vitro oocyte maturation in patients with PCOS: does phenotype have an impact?. Issue 10 (20th September 2020) - Mackens, Shari; Pareyn, Stéphanie; Drakopoulos, Panagiotis; Deckers, Tine; Mostinckx, Linde; Blockeel, Christophe; Segers, Ingrid; Verheyen, Greta; Santos-Ribeiro, Samuel; Tournaye, Herman; De Vos, Michel
Abstract: STUDY QUESTION: Does the phenotype of patients with polycystic ovary syndrome (PCOS) affect clinical outcomes of ART following in-vitro oocyte maturation? SUMMARY ANSWER: Cumulative live birth rates (CLBRs) after IVM were significantly different between distinct PCOS phenotypes, with the highest CLBR observed in patients with phenotype A/HOP (= hyperandrogenism + ovulatory disorder + polycystic ovaries), while IVM in patients with phenotype C/HP (hyperandrogenism + polycystic ovaries) or D/OP (ovulatory disorder + polycystic ovaries) resulted in lower CLBRs (OR 0.26 (CI 0.06–1.05) and OR 0.47 (CI 0.25–0.88), respectively, P = 0.03). WHAT IS KNOWN ALREADY: CLBRs in women with hyperandrogenic PCOS phenotypes (A/HOP and C/HP) have been reported to be lower after ovarian stimulation (OS) and ART when compared to CLBR in women with a normo-androgenic PCOS phenotype (D/OP) and non-PCOS patients with a PCO-like ovarian morphology (PCOM). Whether there is an influence of the different PCOS phenotypes on success rates of IVM has been unknown. STUDY DESIGN, SIZE, DURATION: This was a single-centre, retrospective cohort study including 320 unique PCOS patients performing their first IVM cycle between April 2014 and January 2018 in a tertiary referral hospital. PARTICIPANTS/MATERIALS, SETTING, METHODS: Baseline patient characteristics and IVM treatment cycle data were collected. The clinical outcomes following the first IVM embryo transfer were retrieved, including the CLBR defined as the number of deliveries with at least one live birth resulting from one IVM cycle and all appended cycles in which fresh or frozen embryos were transferred until a live birth occurred or until all embryos were used. The latter was considered as the primary outcome. A multivariate regression model was developed to identify prognostic factors for CLBR and test the impact of the patient's PCOS phenotype. MAIN RESULTS AND THE ROLE OF CHANCE: Half of the patients presented with a hyperandrogenic PCOS phenotype (n = 140 A/HOP and n = 20 C/HP vs. n = 160 D/OP). BMI was significantly different between phenotype groups (27.4 ± 5.4 kg/m 2 for A/HOP, 27.1 ± 5.4 kg/m 2 for C/HP and 23.3 ± 4.4 kg/m 2 for D/OP, P < 0.001). Metformin was used in 33.6% of patients with PCOS phenotype A/HOP, in 15.0% of C/HP patients and in 11.2% of D/OP patients ( P < 0.001). Anti-müllerian hormone levels differed significantly between groups: 12.4 ± 8.3 µg/l in A/HOP, 7.7 ± 3.1 µg/l in C/HP and 10.4 ± 5.9 µg/l in D/OP patients ( P = 0.01). The number of cumulus-oocyte complexes (COC) was significantly different between phenotype groups: 25.9 ± 19.1 COC in patients with phenotype A/HOP, 18.3 ± 9.0 COC in C/HP and 19.8 ± 13.5 COC in D/OP ( P = 0.004). After IVM, patients with different phenotypes also had a significantly different number of mature oocytes (12.4 ± 9.3 for A/HOP vs. 6.5 ± 4.2 for C/HP vs. 9.1 ± 6.9 for D/OP, P < 0.001). The fertilisation rate, the number of usable embryos and the number of cycles with no embryo available for transfer were comparable between the three groups. Following the first embryo transfer, the positive hCG rate and LBR were comparable between the patient groups (44.7% (55/123) for A/HOP, 40.0% (6/15) for C/HP, 36.7% (47/128) for D/OP, P = 0.56 and 25.2% (31/123) for A/HOP, 6.2% (1/15) for C/HP, 26.6% (34/128) for D/OP, respectively, P = 0.22). However, the incidence of early pregnancy loss was significantly different across phenotype groups (19.5% (24/123) for A/HOP, 26.7% (4/15) for C/HP and 10.2% (13/128) for D/OP, P = 0.04). The CLBR was not significantly different following univariate analysis (40.0% (56/140) for A/HOP, 15% (3/20) for C/HP and 33.1% (53/160) for D/OP ( P = 0.07)). When a multivariable logistic regression model was developed to account for confounding factors, the PCOS phenotype appeared to be significantly correlated with CLBR, with a more favourable CLBR in the A/HOP subgroup (OR 0.26 for phenotype C/HP (CI 0.06–1.05) and OR 0.47 for phenotype D/OP (CI 0.25–0.88), P = 0.03)). LIMITATIONS, REASONS FOR CAUTION: These data should be interpreted with caution as the retrospective nature of the study holds the possibility of unmeasured confounding factors and misassignment of the PCOS phenotype. Moreover, the sample size for phenotype C/HP was too small to draw conclusions for this subgroup of patients. WIDER IMPLICATIONS OF THE FINDINGS: Caucasian infertile patients with a PCOS phenotype A/HOP who undergo IVM achieved a higher CLBR than their counterparts with C/HP and D/OP. This is in strong contrast with previously reported outcomes following OS where women with PCOS and hyperandrogenism (A/HOP and C/HP) performed significantly worse. For PCOS patients who require ART, the strategy of OS followed by an elective freeze-all strategy remains to be compared with IVM in a prospective fashion; however, the current data provide support for IVM as a valid treatment option, especially in the most severe PCOS phenotypes (A/HOP). Our data suggest that proper patient selection is of utmost importance in an IVM programme. STUDY FUNDING/COMPETING INTEREST(S): The clinical IVM research has been supported by research grants from Cook Medical and Besins Healthcare. All authors declared no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.